Virtual Dispersive Network in the Prevention of Third Party Interception: A Way of Dealing with Cyber Threat - Ganapathy, Apoorva (ABC Journal of Advanced Research, 2020)
Virtual Dispersive Network (VDN) in preventing third party interception - a way of dealing with cyber threats. VDN is a unique approach to cybersecurity, wherein a signal is transmitted in short bursts or quantum packets, which can't be covertly read without disrupting their content. No one can intercept data sent to you without introducing some noise in it. In this study, we have explored the use of Virtual Dispersive Network in cybersecurity which is still an innovation in the fight against cyberattacks however is still shows considerable potential in reducing cyberattacks on wireless networks drastically.